DEMONSTRATION OF SIGNIFICANT ABIOTIC IRON ISOTOPE FRACTIONATION IN NATURE - Bullen T.D.; White A.F.; Childs C.W.; Vivit D.V.; Schultz M.S. (My University, 2001)
Field and laboratory studies reveal that the mineral ferrihydrite, formed as a result of abiotic oxidation of aqueous ferrous to ferric Fe, contains Fe that is isotopically heavy relative to coexisting aqueous Fe. Because the electron transfer step of the oxidation process at pH >5 is essentially irreversible and should favor the lighter Fe isotopes in the ferric iron product, this result suggests that relatively heavy Fe isotopes are preferentially partitioned into the readily oxidized Fe(II)(OH)x (aq) species or their transition complexes prior to oxidation. The apparent Fe isotope fractionation factor, αferrihydrite- water, depends primarily on the relative abundances of the Fe(II)(aq) species. This study demonstrates that abiotic processes can fractionate the Fe isotopes to the same extent as biotic processes, and thus Fe isotopes on their own do not provide an effective biosignature.